Changing Paradigm in tourism industry: Progress and Emerging issues - Agrawal, Dr. Shikha (IJRDO - Journal of Business Management, 2018)
ABSTRACTWith the start of civilization, human nature is temperamental and full of curiosities. In order to discover change, he wanders from one place to another to know different people, their lifestyles, their culture, their food and everything what he can know about them. The different civilizations all over the world are result of travelling. Even Vasco da Gama discovered sea route to India only through travelling. People travelled from one place to another for pilgrimage, for knowing the ancient culture and for many other reasons.This travelling has now been given the name of tourism. Tourism has now emerged as a full-fledged industry and as per the classification of CSO (Central Statistical Organization) India; it occupies a major place in the service sector. Even with the lack of basic facilities, this industry is flourishing and providing jobs to many along with increasing the Gross Domestic Product.